Control of alternaria brassicicola with thermotherapy and propolis and effect on the physiological quality of kale seeds - Cardoso, Antonio Ismael Inácio [UNESP]; Piacenti, Laura Z. [UNESP]; Lino, Priscilla R. [UNESP]; Padovan, Iasmim M. [UNESP]; Kronka, Adriana Z. [UNESP] (FapUNIFESP (SciELO), 2020)
In the organic production system, the use of agrochemicals for seed treatment is prohibited. This study was carried out to evaluate the effect of heat treatment and propolis on the germination and vigor of kale seeds and the effect on the control of Alternaria brassicicola. In the treatment with wet thermotherapy, three temperatures (50, 55 and 60°C) were evaluated in separated experiments. For each temperature, five immersion times [0 (control), 15, 30, 45 and 60 minutes] were evaluated. In the dry thermotherapy treatment, seeds were submitted to constant 70ºC temperature and five times [0 (control), 24, 48, 72 and 96 hours] were evaluated. In the treatment with propolis, six concentrations (0.0, 0.2, 0.4, 0.6, 0.8 and 1.0%) were studied, with subsequent washing or not washing of the seeds. Then, seeds were inoculated with A. brassicicola and submitted to the following treatments: wet thermotherapy at 50°C for 60 minutes and at 55°C for 15 minutes and propolis at 1.0% with and without further washing. Two control treatments were included in the experiment (inoculated untreated seeds; and not inoculated and untreated seeds), totalizing six treatments. After inoculation and treatments, the incidence of the fungus on the seeds was evaluated and the effect on the physiological quality of the seeds. Both thermotherapy treatments (50°C for 60 minutes and 55°C for 15 minutes) reduced the pathogen incidence significantly. Both propolis treatments at 1% (with and without subsequent washing) did not provide a satisfactory reduction on A. brassicicola incidence in kale seeds. Thermotherapy at 55°C for 15 minutes is the best option for A. brassicicola control in kale seeds, because it does not affect seed physiological quality.
Controle de alternaria brassicicola com termoterapia e própolis e efeito na qualidade fisiológica das sementes de couve
Keywords: Alternative treatments; Brassica oleracea var. acephala; Heat treatment